Research in orthopaedic trauma surgery: approaches of basic scientists and clinicians and the relevance of interprofessional research teams. - Hildebrand, Frank; Höfer, Christine; Horst, Klemens; Friemert, Benedikt; Pennig, Dietmar; Marzi, Ingo; Stange, Richard (European Journal of Trauma & Emergency Surgery, 2023)
Background: An increasing clinical workload and growing financial, administrative and legal burdens as well as changing demands regarding work-life balance have resulted in an increased emphasis on clinical practice at the expense of research activities by orthopaedic trauma surgeons. This has led to an overall decrease in the number of scientifically active clinicians in orthopaedic trauma surgery, which represents a serious burden on research in this field. In order to guarantee that the clinical relevance of this discipline is also mirrored in the scientific field, new concepts are needed to keep clinicians involved in research. Methods: Literature review and discussion of the results of a survey. Results/conclusion: An interdisciplinary and -professional team approach involving clinicians and basic scientists with different fields of expertise appears to be a promising method. Although differences regarding motivation, research focuses, funding rates and sources as well as inhibitory factors for research activities between basic scientists and clinicians exist, successful and long-lasting collaborations have already proven fruitful. For further implementation of the team approach, diverse prerequisites are necessary. Among those measures, institutions (e.g. societies, universities etc.) must shift the focus of their support mechanisms from independent scientist models to research team performances.